Linked low carbon manufacture of cement and precast concrete. (1st May 2013) - Maries, A; Hills, C D; Carey, P; Ostle, S-J
<x xml:space="preserve">Abstract</x> Abstract The novel low carbon scheme for manufacturing cement and concrete proposed in this paper combines three processes. First, a Portland-like cement is made at reduced temperature and cooled so that it self-pulverises to a powder of cement fineness without the need for grinding. Second, CO2 enriched gas is extracted from the cement kiln flue, and this may be used without further refinement in a third part of the process to activate this cement (which is only poorly hydraulic) in the production of precast concrete products. Considerable energy savings are anticipated, and additional sustainability gains arise from the closed loop manufacturing process. Proof of principle has been demonstrated and a preliminary estimate made of CO2 emission reduction: scale-up challenges are still to be addressed. The initial focus is on the production of precast concrete, where there is strong customer demand and regulatory pressure for low embodied carbon cements, together with a need for greater process efficiency. Other potential applications are foreseen in areas such as environmental engineering and non-structural concrete.